S’approprier son genre entre pathologie et résistance. La transidentité après la Révolution islamique en Iran - Azadi, Bahar (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2020)
Keywords: asie; corps; cours; fem3400; identités LGBTQIA2+; iran; islam; personnes trans*; premier cycle; ressource en ligne; régions géographiques; thématiques

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

Ethnocentrisme occidental et perceptions du harem - Ahmed, Leila (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2010)
En 1980, lors de la conférence de la National Women’s Studies Association qui s’est tenue à Bloomington, Indiana, j’ai assisté à une présentation sur « Les femmes dans l’islam » au cours de laquelle je suis intervenue vivement, depuis ma place dans le public, car les intervenantes invitées, trois femmes arabes, présentaient, selon moi un tableau idéalisé de la situation des femmes dans l’islam. Les sociétés islamiques se distinguaient peut-être même plutôt – c’est en tout cas ce que je pensais à l’époque – par le fait qu’elles plaçaient sans équivoque les femmes sous le contrôle des hommes et par le fait qu’elles accordaient aux hommes, de façon tout aussi explicite, le droit à une sexualité et le droit d’exploiter les femmes. Comme le soutenaient les intervenantes, à son avènement l’islam avait apporté un certain nombre de progrès positifs pour les femmes en Arabie. Il avait également accordé certains droits aux femmes tels que le droit à la propriété (qui, en Occident, ne fut accordé aux femmes qu’au dix-neuvième siècle et qui n’est d’ailleurs toujours pas accordé aux femmes selon, parexemple, la loi rabbinique, tout comme le droit de témoigner). Et on ne pouvait certainement pas dire que l’islam était plus malveillant à l’égard des femmes que les deux autres religions monothéistes. Cependant, il me semblait que cela ne justifiait en rien le fait de minimiser la position d’approbation flagrante qui est celle de l’islam en ce qui concerne la supériorité des hommes et le contrôle exercé par ces derniers sur les femmes. Ni d’ailleurs le fait d’occulter les difficultés rencontrées par les femmes, en particulier en ce qui concerne les lois sur le mariage, le divorce et la garde des enfants. Cet article est la traduction de : « Western Ethocentrism and Perceptions of the Harem », Feminist Studies, vol. 8, n°3, autumn 1985, p. 521-534. Cet article a été écrit en 1982 donc avant la disparition de l’Union Soviétique qui date de 1992.
Keywords: approches et analyses; asie; cours; discipline; droits des femmes*; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; occident; orient; premier cycle; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sciences juridiques; sciences sociales; sociologie; stéréotypes; thématiques; voiles islamiques

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Geography of gender in the third world - Momsen, Janet Henshall; Townsend, Janet G. (University of New York Press, 1987)
This pioneering book addresses a key issue in development studies. It follows the influential 'Geography and Gender' as the second collaborative work generated by the Women in Geography Study Groups of the Institute of British Geographers. Its twenty substantive papers explore spatial patterns of gender in Asia, Africa, the caribbean and Latin America. The book's contributors come from Europe, North and South America, India, Sri Lanka, Malaysia, Thailand, Egypt and the Caribbean. 'Geography of Gender in the Third World' analyses the position of women and the societies that ignore and exploit them. it provides both substantial original research and a comprehensive introduction to the geography of gender in low income countries. The book makes a powerful claim for the regional geography of gender.
Keywords: 1900-1999; afrique; amériques; asie; cours; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sud global; thématiques